On China's image constructed from western news coverage of China's humanitarian aid. - Lei Sun (PLoS ONE)
Despite the growing body of research on media representations of China during the COVID-19 outbreak, limited scholarly attention has been devoted to Western news coverage of specific events involving China. Based on a self-built corpus of reports from English-speaking news sources on "China's Humannitarian Aid to Europe (2019-2024)", this study aims to contribute to the scholarship by examining how Western news media represents China's humanitarian aid to Europe, using quantitative and qualitative methods. The study employs corpus-based Critical Metaphor Analysis to analyze how China is linguistically represented through discursive strategies. Guided by the conceptual metaphor THE NATION AS PERSON, the analysis reveals a series of secondary metaphors-including CHINA AS PERSON, EUROPE AS PERSON, and AMERICA AS PERSON. In particular, CHINA AS PERSON is associated with multifaceted images such as "a politician," "an upstart," "a vendor," "an aggressor," and "a dictator," which collectively serve to undermine China's efforts and reframe humanitarian aid as a diplomatic maneuver. This highlights the effectiveness of corpus-assisted CMA in in analyzing media representations of national images amid a global health crisis.